PENETAPAN AWAL BULAN DENGAN METODE ITTIHADUL MATHLA’ DI INDONESIA - Faisal, Nurul Badriyah dan (IAIN LANGSA, 2018)
Determination of the beginning of the month of qamariyah in Indonesia uses several methods, namely ru?yah and hisab. In addition to these methods, to determine the entry of the beginning of the month is also marked by the appearance of hilal in a place (mathla') which is the main key in determining the beginning of the month of qamariyah. Indonesia is one of the majority Muslim countries, and in this case Indonesia is still experiencing differences in worship in that month. The difference between the beginning and end of fasting in Islamic countries is only one portrait of the condition of Muslims. Although they are one ummah, but in a concrete way the Muslims are divided. Apart from being influenced by the method, it is also influenced by differences in mathla? appearance of the moon. Ittuhâdul mathla' method can be used in determining the beginning of the month of qamariyah in Indonesia for the benefit of Muslim societies.